Penerapan Bussiness Intelligence Terhadap Penjualan Vending Machine di Central New Jersey USA Menggunakan Tableau - hilmi, nizar fawwazun; Abdillah, Allif Rizki; Maulana, Putra Syahri; Prakoso, Muhammad Sidiq Bagus (J-INTECH (Journal of Information and Technology), 2024)
This research aims to analyze the application of Business Intelligence (BI) to vending machine sales in Central New Jersey, USA, using the Tableau data visualization tool. In the current digital era, BI is the key for companies to make faster and more precise decisions based on existing data. Vending machines as an automated sales channel produce large and varied sales data, requiring in-depth analysis to improve sales performance. This research uses a case study approach by collecting sales data from a number of vending machines spread across various locations in Central New Jersey. Data is analyzed using Tableau to identify sales patterns, seasonal trends, and factors that influence sales performance. The resulting data visualization helps in revealing important insights such as products with the highest sales, the most effective sales times, and strategic locations for vending machine placement. The research results show that using Tableau in BI is very effective in identifying and analyzing vending machine sales data. These findings provide concrete recommendations for vending machine managers to improve sales strategies, including stock management, pricing, and machine placement. Overall, implementing BI with Tableau provides significant added value in data-based decision making and can be adapted for various other types of business.